Conceptual Change in the Face of Digitalization: Challenges for Workplaces and Workplace Learning - Harteis, Christian; Goller, Michael; Caruso, Carina (Frontiers in Education, 2020)
The article discusses the explanatory power of conceptual change for research on workplace learning in digitalized workplaces. Interestingly, research on conceptual change is well established within the area of science education but widely neglected within the broad area of workplace learning research. Digitalization of work establishes new quality of tasks and tools by integrating workers and machines in digital networks. Hence, conceptual change can be considered as core concept for identifying workers’ successful adaption to digital transformation. Therefore, conceptual change research in the area of workplace learning in digitalized workplaces is highly relevant. The article reflects upon reasons, explores the potential of conceptual change for understanding workplace learning in digitalized workplaces, and illustrates the argumentation by exemplarily referring to digitalized farming. Finally, the article provides suggestions for future research.